Determinants of the profitability of China commercial bank - Chen, Tianle (2019)
With the further opening of Chinese capital markets to foreign banks, Chinese commercial banks are facing huge international competition in the domestic market. The profitability of commercial banks is the most important factor for their survival and development. Therefore, the determinants of the profitability of Chinese commercial banks are of great significance. On the basis of reviewing the research theory of commercial banks' profitability, this paper first introduces the historical background and bank structure of Chinese commercial banks, and then systematically and comprehensively influences the profitability from the perspectives of banks' own factors and external macro-environmental factors. The factors are analyzed by normative research and hypothesis, and the theoretical basis for selecting specific variables and empirical tests is provided. Then, build a commercial bank profitability evaluation index system: profitability (ROAE), asset quality (LLPNIR), capital adequacy (ETA), liquidity problems (LADSTF, NLTA), cost efficiency (CIR), bank size (TA), credit risk (ILGL), macroeconomic conditions (GDP growth, INFLATION). On this basis, using the panel data of 203 major commercial banks from 2013 to 2018, the 2 step General Moment Movement (GMM) model was used for analysis, and then measuring the decisive factors affecting the bank's commercial profitability.